Gastrin Vaccine Alone and in Combination With an Immune Checkpoint Antibody Inhibits Growth and Metastases of Gastric Cancer - Smith, Jill P.; Cao, Hong; Chen, Wenqiang; Mahmood, Kanwal; Phillips, Teresa; Sutton, Lynda; Cato, Allen (Frontiers in Oncology, 2021)
Gastric cancer is a leading cause of cancer-related deaths worldwide. Recently, clinical studies have demonstrated that many of those with advanced gastric cancer are responsive to immune checkpoint antibody therapy, although the median survival even with these new agents is less than 12 months for advanced disease. The gastrointestinal peptide gastrin has been shown to stimulate growth of gastric cancer in a paracrine and autocrine fashion through the cholecystokinin-B receptor (CCK-BR), a receptor that is expressed in at least 56.6% of human gastric cancers. In the current investigation, we studied the role of the gastrin-CCK-BR pathway in vitro and in vivo as well as the expression of the CCK-BR in a human gastric cancer tissue array. CCK-BR and PD-L1 receptor expression and gastrin peptide was found in two murine gastric cancer cells (NCC-S1 and YTN-16) by qRT-PCR and immunocytochemistry. Treatment of NCC-S1 cells with gastrin resulted in increased growth. In vivo, the effects of a cancer vaccine that targets gastrin peptide (polyclonal antibody stimulator – PAS) alone or in combination with a Programed Death-1 antibody (PD-1 Ab) was evaluated in immune competent mice (N=40) bearing YTN-16 gastric tumors. Mice were treated with PBS, PD-1 Ab (50µg), PAS (250µg), or the combination of PD-1 Ab with PAS. Tumor growth was significantly slower than controls in PAS-treated mice, and tumor growth was decreased even more in combination-treated mice. There were no metastases in any of the mice treated with PAS either alone or in combination with PD-1 Ab. Tumor proliferation by the Ki67 staining was significantly decreased in mice treated with PAS monotherapy or the combination therapy. PAS monotherapy or combined with PD-1 Ab increased tumor CD8+ T-lymphocytes and decreased the number of immunosuppressive M2-polarized tumor-associated macrophages. CCK-BR expression was identified in samples from a human tissue array by immunohistochemistry confirming the clinical relevance of this study. These results confirm the significance of the gastrin-CCK-BR signaling pathway in gastric cancer and suggest that the addition of a gastrin vaccine, PAS, to therapy with an immune checkpoint antibody may decrease growth and metastases of gastric cancer by altering the tumor microenvironment.